Lesão no código civil brasileiro e no direito comparado - Bonini, Paulo Rogério (2005)
The juridic institut of injury has always avoided that one of the parties of the busyness relationship have a not proportional gain, takes advantage of the other. The balance among obligations reachs collective goals, resulting of observation of the good will and social function of contracts. The needs of hiring and lack of business knowledge take away willness conscience, considering the lesion like a bad conscience. The cancellation of the business isn t its general purpose, trying to make its conservation with the necessary corrections. There is variability of the effects of injury busyness, sometimes causing absolute nullity, sometimes causing relative nullity, sometimes causing the rescission of the busyness